New blood : third-wave feminism and the politics of menstruation - Bobel, Chris, 1963- (Book collections on Project MUSE., 2010)
"Chris Bobel is a careful ethnographer, respectful of research participants, and while she clearly takes a stand on menstrual activism, she handily defends her proposition that feminism is f̀inding its balance between reliving its past and creating its future.' Bobel's work, which includes incisive analysis of how third-wave, activists incorporate and update tactics and strategies of the second wave, will be a welcome addition to the scholarship of feminism." Elizabeth Kissling, author of Capitalizing on the Curse: The Business of Menstruation.